Study of Na-Montmorillonite–Polyamide Fiber/Polypropylene Hybrid Composite Prepared by Reactive Melt Mixing - Samia Kerakra; Said Bouhelal; Marc Ponçot (International Journal of Polymer Science)
Hybrid composites of polypropylene (PP)/sodium montmorillonite (Na-MMT)/short polyamide fibers (PAfs) were prepared by reactive melt mixing in a Brabender plastograph. To enhance filler interactions within polypropylene, a functionalizing agent (FA) and a coupling agent were added to the Na-MMT and PAfs, respectively. An organic peroxide/sulfur mixture and tetramethylthiuram disulfide as an activator for sulfur were used to functionalize Na-MMT; on the other hand, the PAfs surface was treated using stearic acid. The aim of this study is to investigate how the morphology and the structural properties of 3, 5, and 7 wt% recycled functionalized sodium montmorillonite nanocomposites (f-Na-MMT) are affected by the presence of 5 wt% treated short polyamide fibers (t-PAfs). According to the obtained results, 5 wt% recycled f-Na-MMT/5 wt% t-PAfs/PP hybrid composite showed Na-MMT layers exfoliation. The nucleating effect of f-Na-MMT and t-PAfs was indicated by the differential scanning calorimetry (DSC) measurements. Morphological analysis of the hybrid composites was performed using scanning electron microscope (SEM) and optical polarized microscopy (POM), showing a good dispersion of the fibers with an interesting interfacial adhesion between the PP and t-PAfs phases. Hybrid composites of PP/f-Na-MMT/t-PAfs are considered for automotive industry.